Association between inflammatory proteins and rotator cuff tears: a bidirectional Mendelian randomization study - Yao Wang; Binbin Xu; Chenhao Ma; Donghai Huang; Li Zhou (Scientific Reports)
Abstract Previous research suggests a link between inflammatory proteins and rotator cuff tears, but the specific protein remains unclear. This two-sample Mendelian randomization (MR) study used genetic variants from a genome-wide association study (GWAS) of 14,824 primarily European participants. We analyzed 91 circulating inflammatory proteins using inverse variance weighting (IVW) and validated results with MR-Egger, the weighted median approach, and sensitivity tests. MR analysis identified three inflammatory proteins with significant associations in the IVW analysis: Interleukin-20 (IL-20) levels (OR = 1.225, 95% CI = 1.036 − 1.450, P = 0.044), Leukemia inhibitory factor levels (LIF) (OR = 1.380, 95% CI = 1.008 − 1.889, P = 0.044), and Signaling lymphocytic activation molecule (SLAM) (OR = 1.183, 95% CI = 1.059 − 1.321, P = 0.015). Elevated IL-20, LIF and SLAM increased the risk of rotator cuff tears. This MR study reveals a potential association between IL-20, LIF and SLAM and the risk of rotator cuff tears, providing insights into their pathogenesis and potential therapeutic targets.